2022
DOI: 10.3390/socsci11070272
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of International Scientific Production on the Management of Happiness and Well-Being in Organizations

Abstract: The interest of the scientific community and, consequently, the scientific production of topics on happiness and well-being at work, or the management of happiness in organizations, has been increasing over the years. The main objective of this bibliometric analysis is to determine the evolution of the concepts referred to in published scientific works. Bibliometric methods and techniques are used to analyze the themes and the most relevant trends, the number of papers and their citations, and the main institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Nine of the researchers listed in The questions asked to the participants have been verified in previous works (Jambrino-Maldonado et al, 2022;Rando-Cueto et al, 2022, 2023. Personal face-to-face or telephone interviews were conducted with an average duration of 35-50 min.…”
Section: Results Of Scopus Andmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine of the researchers listed in The questions asked to the participants have been verified in previous works (Jambrino-Maldonado et al, 2022;Rando-Cueto et al, 2022, 2023. Personal face-to-face or telephone interviews were conducted with an average duration of 35-50 min.…”
Section: Results Of Scopus Andmentioning
confidence: 99%
“…After the systematic review of the scientific literature published on "happiness management" and the influence of the environment on the management of happiness in organizations, a bibliometric analysis has been carried out, based on the tools and scientometric indicators (Chen, 2017;Dominko and Verbi c, 2019;Jambrino-Maldonado et al, 2022;S anchez-N uñez et al, 2020). Therefore, this study is based on the previous work carried out by Rando-Cueto et al (2022, 2023 from which it is concluded that more than half of the studies on "happiness management" are related to the environmental setting.…”
Section: Research Design and Methods 21 Bibliometric Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…, 2019a). Last but not least, to show social agents the need for policies in the tourism sector to consider that the culture of happiness management is the light of quality of life, general interest and sustainability (Jambrino-Maldonado et al. , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The biometric analysis carried out by the authors of this article on the philosophy of happiness management reveals that some of its specialists have focused on exploring what kind of leadership is required by a given organisational culture to foster happiness at work in the post-Covid-19 era (Jiménez-Marín et al, 2021 ). Currently, these social science studies are in their embryonic stage of scientific production (Jambrino-Maldonado et al, 2022 ).…”
Section: What Role Can Neuroleadership Play In Happiness Management?mentioning
confidence: 99%